The psychological factors of disabled students’ psychological hardiness - Kuprieieva, Olga (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2020)
The article presents the empirical study on the psychological factors of disabled students’ psychological hardiness. Studying in integrated groups is a challenge of particular difficulty for disabled students who dare to exercise their rights to higher education and equal opportunities proposed by the inclusive environment, which requires from them much more efforts than those in situations of chronic illness, as well as activation of their personal resources. Therefore, it is important to study psychological hardiness as a general indicator of an individual’s mental health, determining their ability to overcome life difficulties. The aim is to study the psychological characteristics, factors and predictors that determine disabled students’ psychological hardiness. Methods. Factor analysis allowed us to determine the parameters of psychological hardiness for disabled students having different intensity of its components. According to the performed regression analysis, the indicators of disabled students’ psychological hardiness having low and medium-high general hardiness are predicted. Results and conclusions. The factor structure of psychological hardiness for disabled students having low intensity of its components includes the following parameters: time perspective; active coping strategies; self-attitude, with the focus on assessment of them from others and an expected positive attitude of others; the need to actualize one’s own Self. The predictors determining these respondents’ psychological hardiness are self-esteem as a source of one’s own strength, the search for social support as a strategy for active overcoming of difficulties, and self-actualization as a need for self-development and self-realization. The factor structure of psychological hardiness for disabled students having medium-high intensity of its components includes the following parameters: meaningful life orientations as a result of existing conscious goals and meanings for their lives; good self-attitude as a determinant of an individual’s internal activity, time perspective as a holistic self-image in time; the individual’s basic beliefs as their implicit ideas about the world around, other people, themselves and relationships with the world; values as an ability to be guided in interaction with the world around by the values of self-actualization. Predictors that determine these respondents’ psychological hardiness are: the future (as a parameter of an individual’s time perspective) and the values of self-actualization. The personality parameters revealed at our empirical research are the resources of disabled students’ psychological hardiness and the condition of their successful self-realization.
Keywords: psychological hardiness; disabled students; personal resources; integrated learning